Application of Vertical Electrical Soundings to Characterize Aquifer Potentials and Subsurface Interpretation in Njikoka and Environs, Anambra State, Nigeria - I, Onyenweife (International Journal of Environmental Sciences, 2023)
Purpose: Geophysical exploration for water table characteristics were carried out in six (6) communities of Njikoka and environs through which water table depth, depth below the water table, thickness of the saturated zone, depth with reference to mean sea level (MSL) and types of aquifer were deduced. The proven geoelectric sections of the study area based on resisitivity from the subsurface and electrical log which confirmed that depth to water table of Njikoka and environs could range from 15 m - 100 m. Depth below the water table in the study area ranged 40 m (around Nimo, Enugu Agidi) to 200 m (Ifitedunu, Ukpo) while the thicknesses of the saturated zones (aquifers) varies from 25 m to 160 m within the respective communities. Depths to Mean Sea Level were delineated to range from - 20 m to - 198 m as obtained from the difference in the water table depths and the heights above sea level which is the elevations. Methodology: Subsurface geophysical exploration was employed in the research of groundwater availability of Njikoka and environs. Schlumberger Vertical Electrical Sounding which is the subsurface geophysical method was carried out only on two locations in each of the communities. The geophysical investigation was made with Earth Resistivity equipment Findings: From the revealed results the study area is dominated with low land topography and prominently composed of unconfined with less cases of confined aquifer as a result of the geological settings of the study area.